Thin-layer vs. semi-infinite diffusion in cylindrical pores: A basis for delineating Fickian transport to identify nano-confinement effects in voltammetry - Ward, K; Xiong, L; Lawrence, N; Hartshorne, R; Compton, R (2013)
Using simulation, voltammetry within a partially electroactive cylindrical pore is investigated. The system studied consists of an insulating cylindrical tube with a ring electrode within its inner circumference, which is filled with electroactive solution, such that electron transfer occurs on the tube's interior surface. The voltammetry is examined in terms of the dimensions of the electrode ring (radius, re, and width, ze) as well as the voltammetric scan rate and the diffusion coefficient of the electroactive species. Four limiting cases are observed. In the limit re←1, the voltammetry varies between that expected for a macro-electrode of equivalent area (as ze←1) and that expected for a microband electrode of equivalent area (as ze←0). In the limit re←0, the voltammetry demonstrates thin-layer behaviour as ze←1. Finally, in the case where re, ze←0, the confinement of the solution leads to the unusual case of planar diffusion towards a micro/nanoscale electrode with a current response that is equivalent to hypothetical 'macro-electrode' of area twice that of the cross sectional area of the cylinder 2πr 2e. The conditions under which these limits operate are defined. © 2013 Elsevier B.V. All rights reserved.